In-situ mechanics of 3D graphene foam based ultra-stiff and flexible metallic metamaterial. (October 2018) - Nautiyal, Pranjal; Mujawar, Mubarak; Boesl, Benjamin; Agarwal, Arvind
Abstract: A 3D macroporous graphene foam based ultra-lightweight, stiff and fatigue-resistant mechanical metamaterial is developed in this study. In-situ indentation of the 3D graphene framework reveals an extraordinary spring constant of ∼15 N/m and an upward of 70% recoverable deformation. The brilliant stiffness and superelasticity of graphene foam is exploited to fabricate Aluminum-based Graphene/Metal Metamaterial by electron beam evaporation. In-situ cyclic indentation inside SEM up to 50 cycles revealed long-distance stress-transfer due to the interconnected network of branches, having spring-like mechanical energy storage ability. The structure is highly fatigue-resistant, with more than 98% of displacement recovery at the end of each loading/unloading cycle. In-situ tensile investigation reveals shearing-type failure with dual-strengthening mechanisms, where stress transfer from Aluminum layer to graphene scaffold enhances the overall load bearing ability and the Aluminum deposit on graphene foam provides a structural backbone that restricts brittle failure. A modified scaling law is proposed for modeling the mechanical strength of cellular metamaterials that takes into consideration the hollow anatomy of graphene frameworks, thereby bridging the current gap in theoretical and experimental foam mechanics. The 3D metamaterial developed in this study can be a game-changing candidate for developing flyweight metallic structures with unprecedented elasticity, stiffness and fatigue-resistance. Graphical abstract: Image 1